CONCEPTION OF GENIE IN THE HIKAYAT TAMIM AD-DARI - Moch. Lukluil Maknun (Widyariset, 2012)
This is a study of the “Hikayat Tamim ad-Dari” which used two theories and two methods: philology andBraginsky’s function. There were three variants of the manuscript that could be reached in the National Libraryof Indonesia. The researcher then selected the three manuscripts and decided the script under the code W. 101to be the primary source according to the criterion of material wideness. The selected manuscript was not onlytransliterated from Jawi into Latin but also edited to be the material for functional analysis. In the editing process,the text containing information of jin was then analyzed, categorized, and described in order to seek the wholeconcept of the jin. The conception revealed from the text were the life of the genie, their physical description, theirstrengthens and weaknesses, their religiosity, their interaction with humans and some creatures associated withthem.